(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
One of the propagation technique for coffee plant production is tissue culture. Tissue culture technique for Coffea arabica L. faces some problems, mainly in the planlet formation regenerated from explants. The objective of this experiment was to examine the effect 2,4-D and 2-ip combination on the formation of direct somatic embryogenesis of Coffea arabica L. in leaves explant. Auxin (2,4-D) and cytokinin (2-ip) concentrations of, respectively, 1; 5 µM and 5; 10; 15; 20 were used as treatments. This research was conducted using completely randomized design with 10 replications. Observation to induce somatic embryos was done by quantitatively on number of callus from explant and number of embryogenic callus. Beside that, observation by qualitative descriptive was also done on deve lopment of embryogenesis. The results showed that Arabica coffee leaves explant of AS 2K clones could be induced in all medium combination except 5µM 2,4-D and 20µM 2-ip combination. Arabica coffee leaves explant of S 795, Sigararutang and AS 1 varieties could be induced in all medium combination. The highest frequency of callus formation was found in AS 2K, Sigararutang and AS 1 varieties on medium containing 1µM 2,4-D in combination with 10µM 2-ip, whereas for the S 795 variety on medium containing 5µM 2,4-D in combination with 10µM 2-ip. The highest frequency of embriogenic callus in all Arabica coffee variety could be reached on medium containing 5µM 2,4-D in combination with 15µM 2-ip. Key words : Coffea arabica L., somatic embryogenesis, 2,4-D, 2-ip, tissue culture, leaves, callus embryogenic.